Work Engagement: The Role of Social Support in Moderating Job Efficacy and Stress in Elementary School Teachers - Happy May Sunday Baiti Rohmah; Pramesti Pradna Paramita; Suryanto Suryanto (Psikostudia : Jurnal Psikologi, 2024)
The results of previous research found that work engagement among teachers was in the low category. Based on the JDR model, there are several aspects that play a role in work engagement, namely: teacher efficacy, work stress and social support. The aim of this research is to see whether social support plays a moderating role in teacher efficacy and work stress on work engagement. The method used is quantitative, through distributing questionnaires using cluster random sampling techniques to measure work engagement, teacher efficacy, work stress and social support among primary school teachers in central Surabaya. The instruments used include Utrecht Work Engagement Scale, Indonesian version of Teachers' Sense of Efficacy Scale, Teacher Stress Inventory, and Multidimensional Scale of Perceived Social Support, then analyzed using Moderated Regression Analysis. As a result, social support provides a moderating role on teacher efficacy and work stress on engagement by 13.9%, which is relatively low. The results of this research can be used as a development tool to increase teacher work engagement by school principals or educational institutions.Hasil penelitian terdahulu ditemukan bahwa keterikatan kerja pada guru berada pada kategori rendah. Berdasarkan model JDR terdapat beberapa aspek yang berperan terhadap keterikatan kerja yakni: efikasi guru, stres kerja dan dukungan sosial. Tujuan dari penelitian ini untuk melihat apakah dukungan sosial berperan memoderasi efikasi guru dan stres kerja terhadap keterikatan kerja. Metode yang digunakan yakni kuantitatif, melalui penyebaran kuisioner dengan teknik cluster random sampling guna mengukur keterikatan kerja, efikasi guru, stres kerja, dan dukungan sosial pada guru sekolah dasar Surabaya pusat. Instrumen yang digunakan mencakup: Utrecht Work Engagement Scale, Indonesian version of Teachers’ Sense of Efficacy Scale, Teacher Stress Inventory, dan Multidimensional Scale of Perceived Social Support, kemudian dianalisis menggunakan Moderated Regression Analysis. Hasilnya, dukungan sosial memberikan peran moderasi pada efikasi guru dan stres kerja terhadap keterikatan sebesar 13,9% yang mana hasil tersebut tergolong rendah. Hasil penelitian ini dapat digunakan sebagai pengembangan peningkatan keterikatan kerja guru oleh kepala sekolah ataupun lembaga pendidikan.